ANALISIS KUALITAS PELAYANAN, PENANGANAN KOMPLAIN DAN CITRA RUMAH SAKIT TERHADAP KEPUASAN PENGGUNA KARTU BPJS DI RUMAH SAKIT DR. OEN SURAKARTA - Fildza Hashifa Tazkiya; Ida Aryati Diah PW; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2019)
The research aims to identify and explain the effect either simultaneously or partially quality of service, complaint handling and image of the hospital against BPJS card user satisfaction in the hospital Dr. Oen Surakarta. This study uses a quantitative research design. The population is the entire card users BPJS in the hospital Dr. Oen Surakarta whose number is infinite. Samples of 100 respondents by sampling using purposive sampling method. A questionnaire was used for data retrieval. Data analysis techniques in this study using multiple linear regression analysis. The results showed that the F test the quality of service, handling complaints and hospital image simultaneously and significantly affect user satisfaction BPJS card at the hospital Dr. Oen Surakarta. T-test results showed that the quality of services and significant impact on user satisfaction BPJS card. Handling complaints had no effect, and to the satisfaction of BPJS card users. the image of the hospital had no effect, and to the satisfaction of BPJS card users. The coefficient of determination indicates the quality of service, complaint handling and image of the hospital has the effect of 59% of the card user satisfaction BPJS in the hospital Dr. Oen Surakarta. Keywords: Quality of Service, Complaint Handling, Image Hospital, User Satisfaction BPJS Cards